Analisis Integrasi Vertikal Pasar Komoditas Cabai Rawit (Capsicum frutescens L.) di Provinsi Sulawesi Tenggara - Setiawan, Indra; Taridala, Sitti Aida Adha; Zani, Munirwan (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2018)
This research is motivated by the unequal production of cayenne pepper in all regency cities in Southeast Sulawesi, Resulting in the distribution to some regions that cause price changes that may occur at any time. Changes in the price of cayenne pepper are used by intermediary traders to manipulate prices at the consumer level and at the producer level, the data shows that between 1992 and 2014 there was a difference between the price of cayenne pepper between the consumer market and the producer market. The purpose of this study was to analyze the vertical integration of commodity market of cayenne pepper (Capsicum frutescens L.) in Southeast Sulawesi. This research was conducted in January 2017 until May 2017. The data used are secondary data sourced from Disperindag and BPS in the form of time series data from 1992 to 2014. The analysis method used is Johansen Cointegration and Vector Error Correction Model (VECM). The results show that the vertical market of cayenne pepper between producers and consumers in Southeast Sulawesi has been integrated with the long term, While in the short term there has been no integration of producer and consumer markets. Where price relation occurs only one direction that producer price influence consumer price while consumer price does not influence producer price, If both markets are interconnected then the market is integrated. Based on this, it is expected that the active role of extension agents and farmer groups to provide price information, So that producers, can know the price information that occurs at the consumer level vice versa.